Gold-catalyzed synthesis of π-extended carbazole-based systems and their application as organic semiconductors - Hendrich, Christoph; Hannibal, Valentin D.; Eberle, Lukas; Hertwig, Leif E.; Zschieschang, Ute; Rominger, Frank; Rudolph, Matthias; Klauk, Hagen; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2021)
Herein we describe a gold-catalyzed bidirectional synthesis of N-heteropolycyclic compounds bearing carbazole moieties - namely π-extended benzodicarbazoles and π-extended indolocarbazoles. Overall, four previously unknown core structures were synthesized. This approach is convergent, modular and the gold-catalyzed key step comprises of a cascade reaction starting from stable di-azido compounds. The obtained molecules were fully characterized and their optical and electronic properties as well as their performance in organic thin-film transistors generated by vacuum deposition were studied. Charge-carrier mobilities of up to 0.3 cm2/Vs were measured.